Challenges of Using Computer-Based Educational Technologies in Higher Education - Makaradze, Nana; Nakashidze-Makharadze, Tatia; Vladimir, Vladimir; Gurgenidze, Marine; Samnidze, Nino; Diasamidze, Medea (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
The level of higher education faces great needs and challenges in the use of computer technology. The technology-based learning process has several important priorities. In particular, the learning process is flexible and comfortable; It is much more exciting and creative; The learning material is comprehensive and teaching/ learning process is of high quality. However, the process, along with the priorities is fraught with many problems and challenges. In this paper, we aim to conduct research and determine what hinders the introduction of computer-based educational technologies and to work out the recommendations for the educators to enhance the quantitative and qualitative quality of the use of computer-based educational technologies. The survey was conducted using online survey, Interview, Focus group and Experiment methods. The following conclusions were made by analyzing the results: students preference is in favor of computer-based educational technologies; Not all the staff implementing higher education programs use computer-based educational technologies in the educational process; HEIs have poorly renovated equipment; The quality does not meet modern requirements; Professors lack of competence; Readiness to actively use computer-based educational technologies and participate in the trainings; To respond the results: It is important to review the training courses in the field of computer technology in the educational programs of HEIs and focus on the use of computer educational technologies; Making a mandatory requirement to use of computer-based educational technologies in the process of planning and implementing educational programs; Plan trainings in the field; To enhance the quality, the studies and surveys should be conducted by HEI quality assurance services.